Health-care cost reduction resulting from primary-care allergy testing in children in Italy - Zethraeus Niklas; Petersson Carl; Dozzi Massimiliano; Borres Magnus P; Vignati Giulio; Fiocchi Alessandro (BMC, 2010)
Abstract Background Allergy places a considerable cost burden on society. Specific immunoglobulin E (spIgE) testing may improve the management of allergy patients. There is therefore a reason to quantify the economic consequences of the use of spIgE testing in the diagnosis of allergic conditions. Methods The expected costs of spIgE testing versus no-testing were calculated using a clinical decision model based on a prospective clinical trial performed in primary care. Results The expected costs per patient over 2 years decreased from 802 euros in the "no-test strategy" to 560 euros in the spIgE "test strategy". Cost savings persisted even after assumptions about the prevalence of allergy and the prices of medications were changed. The "test strategy" increased the percentage of patients correctly diagnosed from 54 to 87%. Conclusions spIgE testing of children with respiratory and/or skin problems in primary care in Italy reduces overall costs to society. These cost savings mostly result from a reduction in the use of medications, particularly corticosteroids. The study indicates that spIgE testing of all children with respiratory and/or skin symptoms would be a cost-effective strategy.